The Relationship between Big Five Personality and Emotion Regulation in Women Who Have Experienced Verbal Violence in Dating - Hadine Azalia; Nurmina (Causalita, 2025)
The purpose of this study was to see the relationship between the big five personality and emotional regulation in women who have experienced verbal violence in dating. In this study, the approach used was a quantitative method with a correlational design. The sample was taken randomly with the criteria, namely women of emerging adulthood age with an age range of 18 to 25 years who had experienced verbal violence in dating relationships, and the relationship had lasted more than six months. The sample of this study amounted to 117 people. The research instruments used were the IPIP-BFM-50 and the Emotion Regulation Questionnaire (ERQ). Product moment analysis was used to analyze the data, and the results showed a strong positive correlation between the dimensions of agreeableness, conscientiousness, and openness to cognitive appraisal strategies in women who had experienced verbal violence in dating and there was no significant correlation between the dimensions of the big five personality and the expressive suppression strategy.